Asymptomatic left ventricular dysfunction with long-term clozapine treatment for schizophrenia: a multicentre cross-sectional cohort study. Issue 1 (26th February 2014) - Chow, V; Yeoh, T; Ng, A C C; Pasqualon, T; Scott, E; Plater, J; Whitwell, B; Hanzek, D; Chung, T; Thomas, L; Celermajer, D S; Kritharides, L
Abstract : Objectives: Patients with schizophrenia treated with clozapine are at risk of acute myocarditis and dilated cardiomyopathy. However, there are no data on the prevalence of subclinical cardiomyopathy or its associations. Methods: 100 consecutive patients with schizophrenia treated with clozapine for >1 year and without a history of cardiac pathology (group 1), 21 controls with a history of schizophrenia treated with non-clozapine antipsychotics for >1 year (group 2) and 20 controls without schizophrenia (group 3) were studied. Comprehensive evaluation by clinical examination, ECG, transthoracic echocardiography including left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) and biochemical profiles were performed. Results: Patients with schizophrenia were of similar age, but had higher body mass index (BMI), rates of smoking and hyperlipidaemia than controls. Patients with schizophrenia had received clozapine or non-clozapine antipsychotics for a mean duration of 6.8±5.3 and 9.7±6.1 years, respectively. Patients taking clozapine demonstrated globally impaired LVEF (58.3%: group 1 vs 62.2%: group 2 vs 64.8%: group 3, p<0.001) and GLS (−16.7%: group 1 vs −18.6%: group 2 vs −20.2%: group 3, p<0.001). Moreover, LVEF was <50% in 9/100 (9%) patients receiving clozapine and in non-clozapine schizophrenia patients or healthy controls, but this was not statistically significantly different (analysis of covariance, p=0.19). Univariate analysis in patients taking clozapine found that impaired LV was not predicted by high-sensitivity troponin T, but was associated with features of the metabolic syndrome (including increased triglycerides, low high-density lipoprotein cholesterol (HDL-C), high-sensitivity C reactive protein and BMI), elevated neutrophil count, elevated heart rate, smoking and N-terminal probrain natriuretic peptide. In patients taking clozapine, multivariable analysis identified elevated neutrophil count and low HDL-C as the only independent predictors of impaired GLS. Conclusions: Asymptomatic mild LV impairment is common in patients with schizophrenia receiving long-term clozapine treatment and is associated with neutrophilia and low HDL-C.